2018
DOI: 10.1021/acs.iecr.8b03872
|View full text |Cite
|
Sign up to set email alerts
|

Copper Ore-Modified Activated Coke: Highly Efficient and Regenerable Catalysts for the Removal of SO2

Abstract: A superior desulfurization catalyst (AC-Cop) was synthesized by blending copper ore and coals through a one-step carbonization–activation process. The sulfur capacities of the modified catalysts were enhanced significantly and that of AC-Cop with 1 wt % of copper ore was 174.8 mg/g, which was 50% higher than that of blank activated coke. Their excellent desulfurization performance could be attributed to the introduction of much more active sites on the surface of AC-Cop, i.e., CuO, Fe2O3, Fe3O4, and CO groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Furthermore, a comparison of the desulfurization performance of CuO−NC at 200 • C in the presence and absence of O 2 (6 vol.%) and H 2 O(g) (6 vol.%) is shown in Figure 7c. The results revealed that both of S/Cu and SO 2 capacity significantly increased in the presence of O 2 , which can be explained by the oxidation of SO 2 and the formation process of sulfates (SO 2 + 1 2 O 2 → SO 3 ; SO 3 + CuO → CuSO 4 ) [18,58]. This process reconfirmed the adsorption mechanism of SO 2 molecules on the oxygen vacancy CuO (111) surface (Figure 6).…”
Section: Adsorption Configuration Of So 2 Molecules On the Oxygen-vac...supporting
confidence: 57%
See 2 more Smart Citations
“…Furthermore, a comparison of the desulfurization performance of CuO−NC at 200 • C in the presence and absence of O 2 (6 vol.%) and H 2 O(g) (6 vol.%) is shown in Figure 7c. The results revealed that both of S/Cu and SO 2 capacity significantly increased in the presence of O 2 , which can be explained by the oxidation of SO 2 and the formation process of sulfates (SO 2 + 1 2 O 2 → SO 3 ; SO 3 + CuO → CuSO 4 ) [18,58]. This process reconfirmed the adsorption mechanism of SO 2 molecules on the oxygen vacancy CuO (111) surface (Figure 6).…”
Section: Adsorption Configuration Of So 2 Molecules On the Oxygen-vac...supporting
confidence: 57%
“…CuO possesses the advantages of high selectivity for SO 2 and renewability, resulting in an excellent performance in SO 2 removal compared with the other metal oxides [14][15][16]. To reduce the amount of metal and economic cost, CuO is usually supported on porous materials and then on the active sites exposed in the flue gas [17][18][19][20][21][22][23]. Tseng et al reported that copper-oxide-supported activated carbon has outstanding performance in SO 2 adsorption and regeneration [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To simplify the preparation and reduce costs, the blending method that integrates AC preparation and catalyzation modification in one step extend the applicability of the catalyst precursor to catch great attention in the past few years. Jiang had prepared the metal oxide-blended activated carbon from walnut shells for flue gas desulfurization 18 , as well as the coal-based AC 13,19 , and the recent work observed clear improvement of SCR activity of the blending-modified AC 20 . However, studies on the SCR application of the blending-modified AC is still in its infancy.…”
mentioning
confidence: 99%
“…Sorption of SO2 on carbonaceous materials provides an alternative in FGD with several advantages such as low capital cost, high operation flexibility and low maintenance cost (Karatepe et al, 2008;Yan et al, 2013;Xu et al, 2016). Many carbonaceous materials have been explored, including biochars, activated carbon, coke, semicoke, and activated carbon fibers, as effective desulfurater for FGD (Li et al, 2008;Zhou et al, 2012;Ding et al, 2015;Gaur et al, 2006;Nieto-Márquez et al, 2016;Shao et al, 2018;Yuan et al, 2018). The previous studies have indicated that microporous structure and surface chemical property of carbon materials are mainly responsible for the effective SO2 removal, especially in the presence of H2O and O2 (Andrey et al, 2002;Raymundo-Piñero et al, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%